Evaluating complex digital resources - Canan Tosunoglu Blake; Clare Davies; Ann Jones; Erica Morris; Eileen Scanlon (Association for Learning Technology, 2003)
Squires (1999) discussed the gap between HCI (Human Computer Interaction) and the educational computing communities in their very different approaches to evaluating educational software. This paper revisits that issue in the context of evaluating digital resources, focusing on two approaches to evaluation: an HCI and an educational perspective. Squires and Preece's HCI evaluation model is a predictive model - it helps teachers decide whether or not to use educational software - whilst our own concern is in evaluating the use of learning technologies. It is suggested that in part the different approaches of the two communities relate to the different focus that each takes: in HCI the focus is typically on development and hence usability, whilst in education the concern is with the learner and teacher use.